Evaluation of Urban Microclimate Parameters as Indicators of Pedestrian Ways Environmental Comfort. Issue 2 (March 2021) - Pilipenko, O; Skobeleva, E; Bulgakov, A
Abstract: A variant of the methodology for quantitatively assessing the availability, comfort and environmental safety of residential areas was proposed by the authors. The principles of creating a biosphere-compatible city, without conflict with the environment and developing a person, were taken as a basis. According to the main provisions of this concept, the degree of implementation of the city's functions is determined by the level of accessibility of these functions for all of its residents, regardless of the characteristics of their health and age. It is proposed to introduce the parameter of time to meet human needs into the system of indicators of master plans as one of the parameters of a comfortable and safe urban environment. It is supposed that socially significant objects of everyday service of residents, as well as open spaces for recreation, should be located on the territory of residential buildings within walking distance at a comfortable distance from the places of residence. At the same time, pedestrian communications in residential areas, in particular those leading from places of residence to the objects under consideration, must comply with environmental safety requirements, as well as open urban spaces for recreation, games, and sport. To assess these parameters an integral indicator, one of the components of which is the predicted level of thermal comfort, was proposed in the work. To determine it, it is proposed to use the bioclimatic index, that is the physiological equivalent temperature (PET). In this work, based on the example of a new residential area in the city of Orel, the corresponding integral indicators were determined in terms of assessing the availability of educational facilities and open green urban spaces, including some points of pedestrian communications. The calculation results showed that when planning a new micro-district, the values of the levels of implementation of city functions in terms of the accessibility of socially significant objects, as well as the levels of comfort and environmental safety of pedestrian communications and open urban spaces, differ significantly from the maximum possible. It is noted that when designing a micro-district and arranging pedestrian communications and open spaces, no attention was paid to ensuring a comfortable climatic regime. Conclusions about the influence of built environment on the temperature regime in the territories of the considered locations are made. It is supposed that expanding the range of indicators for assessing territorial planning projects for analyzing accessibility by time parameter, as well as for assessing the level of environmental safety and comfort, will increase the efficiency of the use of urban planning methods in the planning and development of residential micro-districts in order to create an urban environment that contributes to the preservation of health of residents.